Enhancing Narrative Writing Skills of Elementary School Teacher Education Students through Concentrated Language Encounter (CLE) Model Assisted by Short Film Learning Media - Fauzi, Muhammad Rizal; Wardhani, Duhita Savira; Puspita, Ryan Dwi; Pratama, Deri Fadly; Septian Rahayu, Galih Dani (Mimbar Sekolah Dasar, 2021)
This research aims at improving the narrative essay writing skills of elementary school teacher education students through Concentrated Language Encounter (CLE) learning activities assisted by short film learning media by employing a quasi-experimental nonequivalent group design. The subjects were all primary teacher education students in West Java, with a sample of 31 elementary school teacher education students in Cimahi City as the experimental class, and 31 Madrasah Ibtidaiyah teacher education students in Bandung City as the control class. The results of the post-test research showed that the average skill of writing narrative essays in the experimental class was 81.10, while the control class obtained an average of 66.32. While the test results of the average N-gain difference in writing narrative essay skills with 2-tailed sig were 0.000 with a significance level of less than 0.05. These findings revealed that there was an increase in the writing narrative essay skills of elementary school teacher education students through the application CLE Model assisted by short film learning media. This research is expected to facilitate lecturers/teachers to teach narrative essay writing skills by optimizing all language skills through the CLE model assisted by short film media.